Learn It, Buy It, Work It: Intensive Pregnancy on Instagram - Tiidenberg, Katrin; Baym, Nancy (Social Media + Society, 2017)
This article analyzes how pregnant women perform their pregnancies on Instagram. We ask whether they rely on and reproduce pre-existing discourses aimed at morally regulating pregnancy, or reject them and construct their own alternatives. Pregnancy today is highly visible, intensely surveilled, marketed as a consumer identity, and feverishly stalked in its celebrity manifestations. This propagates narrow visions of what a “normal” pregnancy or “normal” pregnant woman should be like. We argue that pregnant women on Instagram do pregnancy via three overlapping and complimentary discourses of “learn it,” “buy it,” and “work it.” Together these form the current authoritative knowledge of pregnancy we call “intensive pregnancy” as performed on Instagram. Concurrently, this article highlights how the combined discursive power of hashtags, images, and captions may influence and enforce discursive hegemonies.